2022
DOI: 10.1136/bmjnph-2022-000462
|View full text |Cite
|
Sign up to set email alerts
|

Association of periodic fasting with lower severity of COVID-19 outcomes in the SARS-CoV-2 prevaccine era: an observational cohort from the INSPIRE registry

Abstract: ObjectivesIntermittent fasting boosts some host defence mechanisms while modulating the inflammatory response. Lower-frequency fasting is associated with greater survival and lower risk from COVID-19-related comorbidities. This study evaluated associations of periodic fasting with COVID-19 severity and, secondarily, initial infection by SARS-CoV-2.DesignProspective longitudinal observational cohort study.SettingSingle-centre secondary care facility in Salt Lake City, Utah, USA with follow-up across a 24-hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
(136 reference statements)
0
24
0
Order By: Relevance
“…To date, no RCTs have investigated the effects of IF on SARS-CoV-2 infection or severity of COVID-19 outcomes, although epidemiologic evidence regarding periodic fasting suggests that fasting in some forms may prevent severe COVID-19 outcomes such as hospitalization and death [ 71 ], perhaps in part, through the control of hyper-inflammation. The impacts of IF on markers of inflammation and oxidative stress are summarized below:…”
Section: The Potential Impact Of If On Inflammatory Markersmentioning
confidence: 99%
“…To date, no RCTs have investigated the effects of IF on SARS-CoV-2 infection or severity of COVID-19 outcomes, although epidemiologic evidence regarding periodic fasting suggests that fasting in some forms may prevent severe COVID-19 outcomes such as hospitalization and death [ 71 ], perhaps in part, through the control of hyper-inflammation. The impacts of IF on markers of inflammation and oxidative stress are summarized below:…”
Section: The Potential Impact Of If On Inflammatory Markersmentioning
confidence: 99%
“…This intriguing capability includes metabolic improvements that are observed when lower-frequency intermittent fasting is utilized, such as a regimen of once-per-week 24-hour water-only fasting from which substantial weight loss did not occur [ 8 ]. Very low-frequency once-per-month periodic fasting has also been studied in observational analyses for health outcomes of fasting conducted primarily for religious purposes [ 9 , 10 , 14 ]. Such very low-frequency fasting is unlikely to result in substantial weight loss, and observational studies showed that people who reported to routinely engage in such periodic fasting had similar weight and body mass index to those who did not fast routinely [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such very low-frequency fasting is unlikely to result in substantial weight loss, and observational studies showed that people who reported to routinely engage in such periodic fasting had similar weight and body mass index to those who did not fast routinely [ 9 , 10 ]. Many people (35–40%) in those studies who engaged in periodic fasting for religious purposes had participated in the behavior for >40 years (or about 67% of their lifespan) [ 9 , 10 , 14 ], thereby potentially training their bodies to respond optimally to any length of fasting. Associations of periodic fasting were found with lower risks of coronary heart disease and diabetes in cross-sectional observational analyses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations